The Moderating Role of Profitability in The Relationship Liquidity and Leverage on Financial Distress in Islamic Banking - Nur Kholis; Ghozali, Imam; Harto, Puji (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2025)
The purpose of this study is to examine the role of profitability in moderating the relationship between liquidity and leverage on financial distress in Islamic banking. This study uses a quantitative descriptive approach, and the panel data analysis method is implemented using E-views 12. The sample Islamic banking companies listed on The Financial Services Authority (OJK) for a period of four years, namely the 2021-2024 period. The sampling technique employs purposive sampling to collect company data that matches the specified criteria. The results showed that the liquidity ratio does not have a significant effect on financial distress, while leverage has a significant effect on financial distress. Profitability is unable to moderate the relationship between the liquidity ratio and financial distress, but profitability is able to moderate the relationship between leverage and financial distress. The implications of this study help to understand the development and performance of the companies studied and can be used as input and consideration for companies in taking steps to prevent bankruptcy.